Examining the Relationships between Tourists' Connectedness to Nature and Landscape Preferences - Cigdemli, Asli Ozge Ozgen; Avci, Ceren (Cinturs-Research Centre Tourism Sustainability & Well-Being, 2023)
The main purpose of the present research is to examine the relationships between the level of tourists' connectedness to nature (CTN) and their landscape preferences (LP). For this purpose, the study first measures the construct validity and reliability of the CTN scale developed by Mayer and Frantz (2004) to confirm its appropriateness for different cultures and the originally one-dimensional structure of the scale is tested. Second, the LPs of domestic and foreign tourists are determined from six different landscape pictures and a relationship is sought between the tourists' CTN levels and LP. The primary data were gathered through surveys of foreign and domestic tourists staying in Antalya. The relationships between the CTN and LP were determined by multinomial logistic regression analysis (MLRA). According to the findings, as the level of tourists' CTN increases, their preference levels for shopping malls and historical places also increase. It has also been determined that as the CTN increases, preferences for beaches increases, too. Women who prefer shopping malls and historical sites are less likely than men to prefer wildlife. Also, as the preference for historical sites increases, the CTN level increases, too. The results of the study will be beneficial for planners to manage the landscape in destinations and to use the resources effectively.
Keywords: Connectedness to Nature; Landscape Preferences; Tourist; Psychology of Connectedness to Nature; Antalya; Multinomial Logistic Regression Analysis